Going up or getting out? Professional insecurity and austerity in the South African health sector. (May 2020) - Hull, Elizabeth
Abstract: As a precondition of belonging, professionalism is often a taken-for-granted feature of being middle-class. Yet ethnographic attention to experiences of work reveals that professional identity can be fragile. Drawing on ethnographic research among nurses in KwaZulu-Natal, this article traces the feelings of precarity about work and the ambivalence that pervades ideas of professionalism. This ambiguity arises partly out of a peculiarly South African story in which histories of professionalism are entwined with the repressive apartheid project of separate development. Many of the professionals working as teachers, nurses, lawyers and administrators today were trained in the former 'homelands'. Practices of professionalism are entangled with those of clientelism inherited from this earlier period of homeland politics. These local histories combine with wider processes of neoliberalism, as conditions of austerity produce structural shifts towards casualization. The article traces these dynamics in the stories of two nurses and considers what may be at stake politically as middle-class trajectories are threatened. Moving away from a view of the middle classes as either democratic or anti-democratic, feelings of ambivalence about work make questions of political allegiance an ambiguous and fraught matter.